Patterned mesoporous TiO2 microplates embedded in Nafion® membrane for high temperature/low relative humidity polymer electrolyte membrane fuel cell operation. (December 2021) - Nam, Le Vu; Choi, Eunho; Jang, Segeun; Kim, Sang Moon
Abstract: Incorporating inorganic fillers, such as SiO2, TiO2, and CeO2, into the electrolyte membrane via the conventional casting and evaporation process is proved to intensify the water retention, thus improve the proton conductivity of the polymer electrolyte membrane (PEM) under high temperature. However, this approach does not dramatically enhance the performance of the composite membrane due to the issue of proton pathway reduction and fillers agglomeration. Herein, uniformly patterned mesoporous TiO2 microplates (PTMPs) are successfully embedded on the anode side surface of the Nafion® membrane by using micro-hole stencil for spatially localizing the PTMPs and well-controlled ionomer spray technique. Interestingly, the membrane comprised of PTMPs with a diameter of ∼50 μm and a height of ∼5.2 μm exhibits the maximum power density by more than 35.2% compared to the reference Nafion® membrane with the same thickness (∼25 μm) under 120 °C and relative humidity of 35% condition. The result indicates that suitably designed PTMPs-embedded Nafion® membrane is effective for improving the PEMFC performance under elevated temperature and low humidity conditions. Graphical abstract: Image 1